2020
DOI: 10.1007/s40120-020-00181-9
|View full text |Cite
|
Sign up to set email alerts
|

Current Directions in Deep Brain Stimulation for Parkinson’s Disease—Directing Current to Maximize Clinical Benefit

Abstract: Several single-center studies and one large multicenter clinical trial demonstrated that directional deep brain stimulation (DBS) could optimize the volume of tissue activated (VTA) based on the individual placement of the lead in relation to the target. The ability to generate axially asymmetric fields of stimulation translates into a broader therapeutic window (TW) compared to conventional DBS. However, Aristide Merola and Alberto Romagnolo contributed equally to the manuscript and shared co-first authorship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 57 publications
(61 reference statements)
0
23
0
Order By: Relevance
“…In parallel, the connectivity-based selection of stimulation parameters might also prove useful in evaluating the thalamocortical connectivity to optimize the post-surgical programming 38 . This approach is based on anatomically shaping the VTA model with directional DBS systems to optimized target coverage by preferentially steering the electrical field to obtain a better account for any shifts in VIM’s location and shape and improve the therapeutic window at a lower current 39, 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In parallel, the connectivity-based selection of stimulation parameters might also prove useful in evaluating the thalamocortical connectivity to optimize the post-surgical programming 38 . This approach is based on anatomically shaping the VTA model with directional DBS systems to optimized target coverage by preferentially steering the electrical field to obtain a better account for any shifts in VIM’s location and shape and improve the therapeutic window at a lower current 39, 40 .…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of "directional leads" characterized by the middle two (of four) rings divided into three segments has allowed generating an axially asymmetric volume of tissue activation (VTA) tailored to the individual patient's anatomy (67,70). DBS bioelectrical parameters, such as therapeutic impedance and surface current density, are highly dependent on the electrode surface and inevitably change when switching from a circular ring contact to a single-segment activation.…”
Section: Hardware Innovationsmentioning
confidence: 99%
“…Directional DBS has been shown to optimize the volume of tissue activated (VTA) by increasing the therapeutic window (TW) through generating axially asymmetric fields of electrical stimulation (3) via single or multiple segmented leads. Earlier single-center studies (2) and initial results from a multicenter study (3) have also demonstrated the advantages of directional vs. conventional omnidirectional stimulation in increasing the side-effect threshold with a resultant increased TW and lower total electrical energy delivered (TEED). Despite the advantages in delivering better clinical outcomes with less side-effect, directional DBS is still underutilized.…”
Section: To the Editormentioning
confidence: 99%